2013
DOI: 10.1111/nmo.12124
|View full text |Cite
|
Sign up to set email alerts
|

A population‐based study of associations between functional gastrointestinal disorders and psychosocial characteristics in Xi'an, China

Abstract: The prevalence of FGIDs and overlap syndrome in Xi'an, China was lower than that reported in other countries. There was a strong correlation between specific lifestyle habits and psychosocial characteristics and the presence of FGIDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
0
13
0
2
Order By: Relevance
“…When studies were pooled according to the method of administration of the questionnaire, again there were significant differences in prevalence between individual studies. When the Rome III questionnaire was administered at an interview in 29 studies, 20,22,23,31,[33][34][35]37,[39][40][41][42][45][46][47][48][49][51][52][53]60,61,[65][66][67]69,70,75,79 the prevalence of IBS ranged from 0.4% in India and Ghana, 79 to 20.9% in Singapore, 61 with a pooled prevalence of 5.9% (95% CI 4.6% to 7.4%). When the same questionnaire was self-completed in 22 studies 24,28-30,32,36,38,43,44,50,54,56,58,59,62-64,68,71,77-79 the prevalence ranged from 2.0% in the USA, 58 to 29.2% in Croatia, 24 with a pooled prevalence of 12.0% (95% CI 9.6% to 14.6%).…”
Section: Administrationmentioning
confidence: 99%
“…When studies were pooled according to the method of administration of the questionnaire, again there were significant differences in prevalence between individual studies. When the Rome III questionnaire was administered at an interview in 29 studies, 20,22,23,31,[33][34][35]37,[39][40][41][42][45][46][47][48][49][51][52][53]60,61,[65][66][67]69,70,75,79 the prevalence of IBS ranged from 0.4% in India and Ghana, 79 to 20.9% in Singapore, 61 with a pooled prevalence of 5.9% (95% CI 4.6% to 7.4%). When the same questionnaire was self-completed in 22 studies 24,28-30,32,36,38,43,44,50,54,56,58,59,62-64,68,71,77-79 the prevalence ranged from 2.0% in the USA, 58 to 29.2% in Croatia, 24 with a pooled prevalence of 12.0% (95% CI 9.6% to 14.6%).…”
Section: Administrationmentioning
confidence: 99%
“…Detailed characteristics of all the included studies are reported in Supplementary Table 1 . The lowest prevalence (0.25%) and the highest prevalence (38.82%) were reported in two studies ( 47 , 57 ) that used Rome III criteria in the interview-administered questionnaire ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 95%
“…Several studies have investigated different risk factors; [7][8][9] however, no studies have assessed the association among FGIDs, lifestyle habits, and smartphone addiction. Therefore, the present study aimed to assess the prevalence of FGIDs in children aged 11-14 years using the new Rome IV Diagnostic Criteria in a large sample and to investigate their association with lifestyle and smartphone addiction.…”
Section: Introductionmentioning
confidence: 99%